HMGB1: new biomarker and therapeutic target of autoimmune and autoinflammatory skin diseases - Fan, Jinrong; He, Kaiqiao; Zhang, Yonghui; Li, Ruijing; Yi, Xiuli; Li, Shuli (Frontiers in Immunology, 2025)
High-mobility group box 1 (HMGB1) is expressed in almost all human cells. During cell activation and cell death, the nucleoprotein HMGB1 can translocate to the extracellular space, thus mediating the early inflammatory response as an alarmin or damage-associated molecular pattern (DAMP). Extracellular HMGB1 interacts with immune cells by binding to pattern recognition Toll-like receptors (TLRs), including TLR2 and TLR4, and the receptor for advanced glycation end products (RAGE), thus mediating the immune response to protect the host against pathogens and maintain immune balance. HMGB1 is reportedly upregulated and is a critical biomarker for monitoring disease activity in several chronic inflammatory or autoimmune disorders, including multiple sclerosis, rheumatoid arthritis, inflammatory bowel disease, systemic lupus erythematosus and vitiligo. Additionally, the inhibition of HMGB1 expression or its activity has beneficial effects on disease activity in animal models of autoimmune diseases. Thus, HMGB1 is an indispensable biomarker and an important therapeutic target for autoimmune diseases. This review provides a detailed summary of the biological function of HMGB1 and provides a comprehensive outlook in terms of HMGB-focused diagnostic and therapeutic applications in autoimmune skin diseases.